1999
DOI: 10.1021/ma981397i
|View full text |Cite
|
Sign up to set email alerts
|

Poly(styrene) Latex Carrying Cerium(IV)-Initiated Terminally Attached Cleavable Chains:  Analysis of Grafted Chains and Model of the Surface Layer

Abstract: Ce(IV)-initiated grafting of N(2-methoxyethyl-acrylamide) (MEA) to a shell of poly(styrene-co-2-hydroxyethyl acrylate) on polystyrene latex has been performed and the molecular weight distribution of the graft determined by size exclusion chromatography (SEC) on grafted chains cleaved from the surface. Cationic poly(styrene) beads were covered with a shell containing poly(styrene-co-2-hydroxyethyl acrylate) utilizing an azo initiator. The density of the surface hydroxyl groups was assessed by saponification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In fact, the real situation is likely to be more complicated because it is unlikely that all potential sites from which polymerization could be initiated (the aldehyde functions) carry chains of equal length, as is assumed in the calculations. Using CeIV initiation of MEA from cleavable hydroxyl functions on latex surfaces, we recently have shown that the molecular weight distribution of the grafted chains is trimodal, a highly unusual result (24). Nonetheless, such particles also exhibit SEC of proteins analogous to that illustrated here (data not shown).…”
Section: Discussionsupporting
confidence: 56%
“…In fact, the real situation is likely to be more complicated because it is unlikely that all potential sites from which polymerization could be initiated (the aldehyde functions) carry chains of equal length, as is assumed in the calculations. Using CeIV initiation of MEA from cleavable hydroxyl functions on latex surfaces, we recently have shown that the molecular weight distribution of the grafted chains is trimodal, a highly unusual result (24). Nonetheless, such particles also exhibit SEC of proteins analogous to that illustrated here (data not shown).…”
Section: Discussionsupporting
confidence: 56%
“…In particular, the chemistry does not readily permit synthesis of dense polymer brushes where the distance d between grafting sites is considerably less than 2hR g i, where hR g i is the polymer radius of gyration. Precise control of grafted chain length N and polydispersity PDI (¼M w /M n ) is also very difficult (Hritcu et al, 1999). Many of these problems can be addressed through the use of surface-initiated atom transfer radical polymerization (ATRP), which permits synthesis of a wide range of grafted polymer layers with high graft density, low PDI, and desired number-average molecular weight (M n ).…”
mentioning
confidence: 99%
“…For polymer layers grafted onto silica surfaces, hydrofluoric acid has been used to dissolve the base silica matrix and thereby release the grafted polymers into solution (Chaimberg and Cohen, 1991;Ejaz et al, 2001;Huang and Wirth, 1999;Khan and Huck, 2003;Liu et al, 2003). There are also novel ways to grow polymers on ester linkers, allowing the grafts to be cleaved by saponification (Hritcu et al, 1999;Husseman et al, 1999;Jayachandran and Chatterji, 2000;Jayachandran et al, 2002;Kizhakkedathu and Brooks, 2003). This latter approach has the advantage that it can be used to tune the graft density by partial saponification of the polymer layer.…”
mentioning
confidence: 99%
“…Amphiphilic core‐shell particles are also of interest from a fundamental and academic point of view, especially in the area of colloid and interface science. Such particles have been prepared according to four general approaches: (1) stepwise deposition of polyelectrolytes onto charged particle surfaces;7–10 (2) self‐assembly of amphiphilic block copolymers followed by covalent crosslinking of the shells to form shell‐cross‐linked “knedel” (SCK) micelles;11–16 (3) graft copolymerization of hydrophilic monomers onto reactive seeded particles;17–21 and (4) free radical copolymerization of hydrophilic macromonomers or surfmers with hydrophobic monomers 22–26. Despite the success of these approaches, there are still some drawbacks, such as time consuming sequential polyelectrolyte deposition cycles and purification steps, tedious multiple‐step syntheses, and the use of hydrophilic monomers, resulting in low surface incorporation and the formation of a large amount of water‐soluble homopolymers.…”
Section: Introductionmentioning
confidence: 99%